The Fundamental Ontology of Study. Issue 2 (April 2014) - Lewis, Tyson E.
Abstract In an effort to disrupt the hegemonic dominance of learning theory, in this article Tyson Lewis explores the unique educational logic of studying. Drawing on the work of Giorgio Agamben, we can understand the operation of study as one of suspension through three modes: preferring not; no longer, not yet; and as not. But the relationship between the operation of suspension and the everyday mode of learning remains an open question requiring further analysis. In order to accomplish this task, it is important to remember that for Agamben, study is a kind of profanation or improper life. Through examining Heidegger's analytic of Dasein's everyday being, Lewis demonstrates that the nature of study is always already saturated with the everyday, and is itself a contaminated process that is neither simply everyday living nor "authentic" existence. To be absolutely precise, the studier engages in idle talk, is curious, and is caught up in ambiguity in order to explore the seemingly uninhabitable zone that rests between everyday falling and authentically standing. Lewis concludes by offering Agamben's own work as a paradigm of study, illustrating how the smallest of freedoms opens to the studier: the freedom to dwell in potentiality.